Employers' Perspectives on Hiring and Accommodating Workers With Mental Illness. (14th August 2014) - Shankar, Janki; Liu, Lili; Nicholas, David; Warren, Sharon; Lai, Daniel; Tan, Shawn; Zulla, Rosslynn; Couture, Jennifer; Sears, Alexandra
Many individuals with mental illness want to return to work and stay in employment. Yet, there is little research that has examined the perspectives of employers on hiring and accommodating these workers and the kinds of supports employers need to facilitate their reintegration into the workforce. The aim of the current research was to explore the challenges employers face and the support they need to hire and accommodate workers with mental illness (WWMI). A qualitative research design guided by a grounded theory approach was used. In-depth interviews were conducted with 28 employers selected from a wide range of industries in and around Edmonton, Canada. The employers were a mix of frontline managers, disability consultants, and human resource managers who had direct experience with hiring and supervising WWMI. Data were analyzed using the principles of grounded theory. The findings highlight several challenges that employers face when dealing with mental health issues of workers in the workplace. These challenges can act as barriers to hiring and accommodating WWMI.